Чудеса превращений - Дюма А. (Литературные сказки для младших школьников)
Экземпляры: ф.6 (2013) / Инвентарный номер: 55131 / Цена: 198.00 / Сис.шифр: 84(4) / Авт.знак: Ч-84 / ГРНТИ: 17.82.93 / ББК: 84(4)